Overview of AI in finance - Lopez-Lira, Alejandro (Henry Stewart Talks, 2024)
Algorithmic trading, Risk management, Credit scoring, Portfolio management, Predicting future outcomes, Patterns and relationships in data, Machine learning, Natural language processing (NLP)